The Mass Calculation of Solitary Wave Solution of the One-Dimensional Burgers Equation - Teguh B. Prayitno (POSITRON, 2012)
We have calculated the mass of the solitary wave solution of the one-dimensional Burgers equation by integrating the Hamiltonian density of its equation based on the formulation of the classical field theory. To use this method, we first construct the Lagrangian density in order to obtain the Hamiltonian density by initially introducing the ansatz function of the appropriate field. In this paper, we have obtained that the mass of the solitary of the one-dimensional of Burgers equation is literally divergent.